2018
DOI: 10.1007/s40090-018-0158-z
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemically assisted photocatalytic removal of m-cresol using TiO2 thin film-modified carbon sheet photoelectrode

Abstract: In this study, removal of m-cresol has been performed using photoeletrocatalysis technique at the surface of titanium dioxide (TiO 2) thin film-modified carbon sheet photoelectrode. A biased potential was applied across this photoelectrode illuminated by UV light to investigate the feasibility of an electrochemically assisted photocatalytic process in this degradation. For preparation of this photoelectrode, the photocatalytically active TiO 2 thin film was covered on the carbon sheet by dip coating technique … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 49 publications
0
0
0
Order By: Relevance
“…Again, the influence was similar for DCF and SA solutions (Figure 1a,b) and different for the MEM solution (Figure 1c,d). The responses of irradiated TiO 2 electrodes in DCF and SA solutions show a current peak similar to that of the dark characteristic, as well as a decrease in the current compared to the current in the NaCl solution [35,43]. The decrease in current can be explained by the adsorption of SA and DCF on the electrode surface, blocking the surface-active sites.…”
Section: Resultsmentioning
confidence: 73%
See 1 more Smart Citation
“…Again, the influence was similar for DCF and SA solutions (Figure 1a,b) and different for the MEM solution (Figure 1c,d). The responses of irradiated TiO 2 electrodes in DCF and SA solutions show a current peak similar to that of the dark characteristic, as well as a decrease in the current compared to the current in the NaCl solution [35,43]. The decrease in current can be explained by the adsorption of SA and DCF on the electrode surface, blocking the surface-active sites.…”
Section: Resultsmentioning
confidence: 73%
“…Electrochemical techniques can be a powerful tool in the field of PC or PEC, enabling material and material/solution interface characterisation. A review of the literature has indicated that a large number of reports are related to the photocatalyst characterisation by electrochemical methods; however, reports related to the influence of pharmaceuticals on the photocatalyst electrochemical response are still scarce [11,31,33,35,43,44]. The aim of this work was an examination of the influence of pharmaceuticals (DCF, MEM and SA) on the PEC response of TiO 2 , TiO 2 /SnS 2 and SnS 2 photoactive materials using simple and fast electrochemical methods.…”
Section: Introductionmentioning
confidence: 99%